Reaction of different Capsicum genotypes to four viruses - Kazinczi, G.; Kovács, J.; Takács, A. P.; Horváth, J.; Gáborjányi, R. (International Journal of Horticultural Science, 2003)
The objective of this study was to examine the reaction of 44 Capsicum genotypes to common strain of Tobacco mosaic virus (TMV-C/U1), Obuda pepper virus (ObPV), NTN strain of Potato virus Y (PVYNTN) and legume strain of Cucumber mosaic virus (CMVU/246). Reaction (extreme resistance, hypersensitive reaction, latent susceptibility, susceptibility) of the tested Capsicum species/hybrids and breeding lines seemed to be greatly depending on hosts and viruses. Out of the breeding materials 4/99 F2 and IX-8 in to CMV-U/246, while 32.Bogyisz. type, VI-57 ii. 57/83 and V-12=19/98 to TMV-C/Ui showed extreme resistance. Two lines (V-25 F1=32/98 F1 and V-27 in F4=35/98 F4) showed hypersensitive reaction to ObPV. Latent susceptibility to PVYNTN was observed in case of all eleven tested Capsicum genotypes and in case of several lines to TMV-C/U1, ObPV and CMV-U/246. Other breeding materials proved susceptible to the mentioned viruses. Pepper genotypes showing extreme resistance and hypersensitivity could be used for resistance breeding to viruses.